2015
DOI: 10.1007/s11948-015-9723-4
|View full text |Cite
|
Sign up to set email alerts
|

Research Ethics in the Context of Transition: Gaps in Policies and Programs on the Protection of Research Participants in the Selected Countries of Central and Eastern Europe

Abstract: This paper examines the ability of countries in Central and Eastern Europe (CEE) to ensure appropriate protection of research participants in the field of increasingly globalizing biomedical research. By applying an analytical framework for identifying gaps in policies and programs for human subjects protection to four countries of CEE – Belarus, Latvia, Lithuania, and Poland, substantial gaps in the scope and content of relevant policies and major impediments to program performance have been revealed. In thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Based on a review of public documents and a survey of RECs, Famenka, an alumnus of the Advanced Certificate Program, described the research ethics review system in Belarus and identified deficiencies in policy implementation and plausibility (Famenka, 2011(Famenka, , 2014.…”
Section: Examples From Belarusmentioning
confidence: 99%
“…Based on a review of public documents and a survey of RECs, Famenka, an alumnus of the Advanced Certificate Program, described the research ethics review system in Belarus and identified deficiencies in policy implementation and plausibility (Famenka, 2011(Famenka, , 2014.…”
Section: Examples From Belarusmentioning
confidence: 99%
“…If the accession numbers have not yet been obtained at the time of submission, please state that they will be provided during review. They must be provided prior to publication [46][47][48][49][50].…”
Section: Analysis Of the Polish Energy And Electromobility Marketmentioning
confidence: 99%
“…In the decades since, many countries have used international guidelines as a starting point for constructing national research ethics systems, including IRBs to enforce research ethics review (Famenka, 2016). Despite an increasing number of countries following international research ethics guidelines, IRBs globally still face numerous obstacles in achieving their goal of improving the protection of research participants (Famenka, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Standard guidelines for research ethics involving human subjects were largely determined by international consensus following World War II, including the Nuremberg Code in 1947, the Declaration of Helsinki in 1964, and more recently, the Good Clinical Practice (GCP) guidelines developed by the International Conference on Harmonisation (ICH). In the decades since, many countries have used international guidelines as a starting point for constructing national research ethics systems, including IRBs to enforce research ethics review (Famenka, 2016). Despite an increasing number of countries following international research ethics guidelines, IRBs globally still face numerous obstacles in achieving their goal of improving the protection of research participants (Famenka, 2016).…”
Section: Introductionmentioning
confidence: 99%